Urinary miRNA Profiles in Chronic Kidney Injury—Benefits of Extracellular Vesicle Enrichment and miRNAs as Potential Biomarkers for Renal Fibrosis, Glomerular Injury, and Endothelial Dysfunction. (4th March 2022) - Petzuch, Barbara; Bénardeau, Agnès; Hofmeister, Lucas; Meyer, Jutta; Hartmann, Elke; Pavkovic, Mira; Mathar, Ilka; Sandner, Peter; Ellinger-Ziegelbauer, Heidrun
Abstract: Micro-RNAs (miRNAs) are regulators of gene expression and play an important role in physiological homeostasis and disease. In biofluids, miRNAs can be found in protein complexes or in extracellular vesicles (EVs). Altered urinary miRNAs are reported as potential biomarkers for chronic kidney disease (CKD). In this context, we compared established urinary protein biomarkers for kidney injury with urinary miRNA profiles in obese ZSF1 and hypertensive renin transgenic rats. Additionally, the benefit of urinary EV enrichment was investigated in vivo and the potential association of urinary miRNAs with renal fibrosis in vitro . Kidney damage in both rat models was confirmed by histopathology, proteinuria, and increased levels of urinary protein biomarkers. In total, 290 miRNAs were elevated in obese ZSF1 rats compared with lean controls, whereas 38 miRNAs were altered in obese ZSF1 rats during 14–26 weeks of age. These 38 miRNAs correlated better with disease progression than established urinary protein biomarkers. MiRNAs increased in obese ZSF1 rats were associated with renal inflammation, fibrosis, and glomerular injury. Eight miRNAs were also changed in urinary EVs of renin transgenic rats, including one which might play a role in endothelial dysfunction. EV enrichment increased the number and detection level of several miRNAs implicated in renal fibrosis in vitro and in vivo . Our results show the benefit of EV enrichment for miRNA detection and the potential of total urine and urinary EV-associated miRNAs as biomarkers of altered kidney physiology, renal fibrosis and glomerular injury, and disease progression in hypertension and obesity-induced CKD.